Research on the Impartment and Inheritance of Tea-picking Dance in Southeastern Guangxi - Xie, Li; Dang, Wei-Bo (Journal of Ecohumanism, 2024)
The Tea-picking Dance of Southeast Guangxi Intangible Cultural Heritage project has great local characteristics and high cultural value. However, the current situation of protection and inheritance is not optimistic. Countermeasures research on the protection and inheritance of Tea-picking Dance of Southeast Guangxi is conducive to further improving the Intangible Cultural Heritage related disciplinary system, providing countermeasures references for local intangible cultural heritage protection and inheritance, and at the same time is conducive to empowering rural revitalization and promoting the economic development of the region.This paper uses the methods of literature investigation, interviewinvestigation and SWOT-AHP to carry out weight analysis and explore the dilemma of protection and inheritanceThe research results show that there are certain dilemmas in the protection and inheritance of Tea-picking Dance of Southeast Guangxi. Such as the lack of innovative content, the aging phenomenon of the inheritors, the lack of inheritance awareness, the lack of Intangible Cultural Heritage staff, the low application of digital protection, the lack of cooperation between theIntangible Cultural Heritage protection departments, and the lack of the development of cultural industry chain for the Tea-picking Dance. Based on this, the constructive countermeasures for the Intangible Cultural Heritage protection and inheritance of the Tea-picking Dance of Southeast Guangxi are proposed, hoping to provide a path reference for the protection and inheritance of other Intangible Cultural Heritage projects in China.